Penerapan Model Teoritis Penyesuaian Kurikulum ABK - Lusi Jumianti; Peri Mulyadi; Opi Andriani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to develop a curriculum modification model for children with specialneeds and determine the empirical validity of curriculum modification. Data collection wascarried out through observation. The data analysis method uses descriptive qualitative, which inthis method discusses the process of in-depth communication interaction between the researcherand the phenomenon to be discussed. In this research, the preparation of the ABK curriculumuses a theoretical model. Creating a theoretical model usually involves analyzing the subject's literature, including previous research studies and journal articles.